The Effect of Social Behaviors Training on Improvement of the Social Skills of Adolescents with Intellectual Disability - Seyyedeh Somayyeh Jalil-Abkenar; Mohammad A'shouri; Gholam Ali Afrouz (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: The purpose of the research was to investigate the effectiveness of social behaviors training on improvement of the social skills of 14-18 years old girl adolescents with intellectual disability in Mazandaran province. Materials & Methods: In this semi-experimental study with pretest and posttest design with control group, were selected fourty girl adolescents with intellectual disablity of 14-18 years old through multi-stage cluster sampling method. Subjects allocated randomly to two groups (experimental and control) and each group consist of 20 individuals. Experimental group attended in social behaviors training in the 8 sessions lasting for 90 minutes on the one month, but the control group did not receive any of instruction. The instruments consist of Revan intelligence test and Matson's social skills scale. The data analysis was done by using MANCOVA. Results: The findings of this research showed that there were a significantly increasing in the mean scores of social skills (P<0.05). Also, scores mean of all of the social skills subscales (appropreate social skills, asocial behaviors, impulsive & aggression, superiority & high self-confident and relation with peers) significantly increase on the post intervention in experimental group (P<0.05). Conclusion: The social behaviors training program lead to improve social skills of adolescents with intellectual disability. Therefore, planning for social behaviors training has a particular importance for adolescents with intellectual disability.